Control of mRNA Splicing by Intragenic RNA Activators of Stress Signaling: Potential Implications for Human Disease - Kaempfer, Raymond; Ilan, Lena; Cohen-Chalamish, Smadar; Turgeman, Orli; Namer, Lise Sarah; Osman, Farhat (Frontiers in Genetics, 2019)
A critical step in the cellular stress response is transient activation of the RNA-dependent protein kinase PKR by double-helical RNA, resulting in down-regulation of protein synthesis through phosphorylation of the α chain of translation initiation factor eIF2, a major PKR substrate. However, intragenic elements of 100-200 nucleotides in length within primary transcripts of cellular genes, exemplified by the tumor necrosis factor (TNF)-α gene and fetal and adult globin genes, are capable of forming RNA structures that potently activate PKR and thereby strongly enhance mRNA splicing efficiency. By inducing nuclear eIF2α phosphorylation, these PKR activator elements enable highly efficient early spliceosome assembly yet do not impair translation of the mature spliced mRNA. The TNF-α RNA activator of PKR folds into a compact pseudoknot that is highly conserved within the phylogeny. Upon excision of β-globin first intron, the RNA activator of PKR, located in exon 1, is silenced through strand displacement by a short sequence within exon 2, restricting thereby the ability to activate PKR to the splicing process without impeding subsequent synthesis of β-globin essential for survival. This activator/silencer mechanism likewise controls splicing of α-globin pre-mRNA, but the exonic locations of PKR activator and silencer sequences are reversed, demonstrating evolutionary flexibility. Impaired splicing efficiency may underlie numerous human β-thalassemia mutations that map to the β-globin RNA activator of PKR or its silencer. Even where such mutations change the encoded amino acid sequence during subsequent translation, they carry the potential of first impairing PKR-dependent mRNA splicing or shutoff of PKR activation needed for optimal translation.